Complete Reconstruction of the Left Heart with Atriomegaly and Ventriculomegaly: Clinical Case - Popov, Volodymyr V.; Boukarim, Valery Zh.; Bolshak, Oleksandr O.; Khoroshkovata, Olena V.; Yuvchyk, Olena V. (Ukrainian Journal of Cardiovascular Surgery, 2022)
Implementation of the principles of medical preparation, comprehensive reconstruction of the left heart in patients with atriomegaly and ventriculomegaly and combined mitral-tricuspid valve diseases leads to improvement of myocardial function and morphometric parameters of the left atrium (LA) and left ventricle (LV). Case description. Patient R., male, 67 years old, underwent examination and treatment from April 22 to May 25, 2021 at the department of surgical treatment of acquired heart diseases of the National Amosov Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine with the diagnosis of stage IV mitral regurgitation, stage IV tricuspid insufficiency, high grade pulmonary hypertension, permanent atrial fibrillation (lasting 10 years since 2011), IIB heart failure with reduced left ventricular ejection fraction (LVEF), secondary hypothyroidism (state of drug subcompensation). Upon admission, the patient was in a state of circulatory decompensation, which required long-term medical preparation for the operation. After his condition was improved, the patient underwent surgery: mitral valve replacement with complete preservation of the valve apparatus, triangular plasty of LA, tricuspid valve plasty with the imposition of a support ring and resection of the right atrium. There were no complications during the intraoperative period. The postoperative period was characterized by symptoms of hyperbilirubinemia, increased exudation from drainages on the first day after surgery. After appropriate treatment, the patient’s condition was stabilized. The patient was discharged on the 13th day after surgery with improvement. Conclusion. Given the initial severe condition of the patient with advanced heart disease with reduced LVEF, left atriomegaly 9.5x12.3 cm, high grade pulmonary hypertension (peak systolic pressure = 70 mm Hg) and comorbidities, comprehensive reconstruction of the left heart with atriomegaly and ventriculomegaly leads to improvement of functional state of the myocardium and morphometric parameters of LA and LV.